2016
DOI: 10.1111/liv.13322
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hepatitis C recurrence by bridging sofosbuvir/ribavirin from pre‐ to post‐liver transplant: a real‐life strategy

Abstract: In patients with suboptimal virological response at LT, a bridging SOF/R regimen helps avoiding post-transplant graft reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…HCC was present in 107 patients (48%). As expected, MELD and Child-Pugh score were lower in HCC than non-HCC patients (MELD: 10.5 [6-23] vs 15 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], Child-Pugh: 7 [5][6][7][8][9][10][11][12] vs 8 [7][8][9][10][11][12] respectively). Nine patients were also positive for the anti-…”
Section: Patientsmentioning
confidence: 60%
See 1 more Smart Citation
“…HCC was present in 107 patients (48%). As expected, MELD and Child-Pugh score were lower in HCC than non-HCC patients (MELD: 10.5 [6-23] vs 15 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], Child-Pugh: 7 [5][6][7][8][9][10][11][12] vs 8 [7][8][9][10][11][12] respectively). Nine patients were also positive for the anti-…”
Section: Patientsmentioning
confidence: 60%
“…The median time to clearance was 4 weeks (min/max 1-28). Seventeen (7.6%) patients received LT (median treatment duration 4 [0-13] weeks) or discontinued prematurely the drugs (median treatment duration 6 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] weeks) when they were still viraemic; two patients failed to clear HCV-RNA and one patient showed a virological breakthrough.…”
Section: Clinical and Virological Outcomesmentioning
confidence: 99%
“…In the treatment of patients with HCC and HCV, the main goal of DAA has been to prevent HCV reinfection after LT . Pre‐LT DAA therapy effectively prevented HCV recurrence in 95% of 61 Child‐Pugh A patients, providing a minimum 30‐day period of viral suppression elapsed before LT. A bridging strategy enabled graft reinfection to be prevented in most of the patients enrolled in the Italian ITACOPS study . No solid data exist at present on whether preventing decompensation by eradicating the virus would enable the use of downstaging therapies for HCC.…”
Section: How To Deal With Direct‐acting Antiviral Treatment Failure Bmentioning
confidence: 99%
“…Child-Pugh A patients, providing a minimum 30-day period of viral suppression elapsed before LT. A bridging strategy enabled graft reinfection to be prevented in most of the patients enrolled in the Italian ITACOPS study. 165,170 No solid data exist at present on whether preventing decompensation by eradicating the virus would enable the use of downstaging therapies for HCC.…”
Section: How To De Al With D Irec T-ac Ting Antivir Al Tre Atment Fmentioning
confidence: 99%
“…Donato et al (17) reported that of 31 patients treated with sofosbuvir (400 mg/day) and ribavirin (600-1200 mg/day) for 24 to 48 weeks before liver transplantation, HCV was eradicated in 12 before liver transplantation.…”
Section: Sofosbuvir-based Therapymentioning
confidence: 99%